Study of the nozzle check valve with respect to its operating characteristics - Klas, Roman; Habán, Vladimír; Rudolf, Pavel (EPJ Web of Conferences, 2018)
Several modifications were developed when designing the nozzle valve. This study offers an assessment of the properties of new modifications of the nozzle valve design. The main operating characteristics, such as loss and flow coefficients, were determined using a CFD methods. Besides mentioned coefficients, the forces acting on the valve disc are also decisive for the behavior of the valve, both in its steady and unsteady operation. It is important to examine the possible simplification and matching of CFD simulation results from 2D and 3D geometries in terms of subsequent dynamic analysis of the valve. This will be taken into consideration by comparing the above-mentioned operating characteristics, by analyzing the forces acting on the valve disc and comparing the velocity and pressure fields.

Several modifications were developed when designing the nozzle valve. This study offers an assessment of the properties of new modifications of the nozzle valve design. The main operating characteristics, such as loss and flow coefficients, were determined using a CFD methods. Besides mentioned coefficients, the forces acting on the valve disc are also decisive for the behavior of the valve, both in its steady and unsteady operation. It is important to examine the possible simplification and matching of CFD simulation results from 2D and 3D geometries in terms of subsequent dynamic analysis of the valve. This will be taken into consideration by comparing the above-mentioned operating characteristics, by analyzing the forces acting on the valve disc and comparing the velocity and pressure fields.
Study of the nozzle check valve with respect to its operating characteristics
Keywords: CFD simulations; nozzle check valve; flow coefficient; force; disc; CFD simulations; nozzle check valve; flow coefficient; force; disc